An Analysis of Difficulties in Learning English Speaking Among Sixth Grade Students at SD Negeri 1 Kawan - Setianingsih, Luh Ayu; Adiwijaya, Pande Agus; Numertayasa, I Wayan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study analyzes the difficulties faced by sixth-grade students at SD Negeri 1 Kawan in learning to speak English. The aim is to identify specific challenges related to vocabulary, pronunciation, and grammar that hinder students’ speaking performance. This research uses a qualitative approach, with data collected through observations, interviews, questionnaires, and documentation, involving 28 students and one English teacher. The findings reveal that students often struggle with finding the correct vocabulary, producing accurate pronunciation, and applying appropriate grammar during speaking activities. These difficulties are exacerbated by low self-confidence, limited exposure to English, and a lack of interactive speaking practice. The study underscores the importance of implementing engaging, student-centered teaching strategies, such as role-play, games, and collaborative activities, to create a supportive environment that encourages active participation. The results of this research are expected to offer valuable insights for teachers and stakeholders in designing more effective and contextual English learning programs, particularly for elementary school students.